RETRACTED : The Influence of Product Quality, Brand Image and Celebrity Endorsers on the Decision to Purchase Sunsilk Shampoo at Indomaret South Jakarta Sunday Market Area - Mega Yunita; Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This research aims to determine the influence of product quality, brand image and celebrity endorser on purchasing decisions for Sunsilk shampoo in the Pasar Minggu area, South Jakarta. The research method used in this research is descriptive quantitative with the population in this research being Indomaret consumers who use Sunsilk shampoo at Indomaret in the Pasar Minggu area, South Jakarta. There are 4 (four) variables examined in this research, namely Product Quality (X1), Brand Image (X2), and Celebrity Endorser (X3) as independent variables, and Purchase Decision (Y) as the dependent variable. The sample used in this research was 100 respondents. This research data uses primary data by distributing questionnaires using the multiple linear regression method which is processed using SPSS 17.0 software. Research results based on multiple linear regression analysis show that Product Quality (X1), Brand Image (X2) and Celebrity Endorser (X3) have a positive and significant effect on Purchasing Decisions (Y).